Rancang Bangun Alat Peraga Ground Lock Main Landing Gear - Fadli Hidirsyah; Mufti Arifin; Riskha Agustianingsih (FTK UNSURYA, 2024)
The Landing gear is a critical component of an aircraft that supports its weight and absorbs shocks during takeoff and landing, as well as reduces air resistance during flight. The Ground Lock is a crucial part that locks the Landing gear in place when the aircraft is parked to ensure stability. For educational purposes, a practical and portable model has been created that resembles the actual Landing gear, with dimensions adjusted for classroom use (31.5 cm x 21.2 cm x 18.4 cm). This model uses flexible hydraulic hoses and medical syringes as hydraulic pumps, with a frame made of strong, lightweight, and transparent aluminum and acrylic. Testing of the model shows that this hydraulic system is effective in simulating the locking and releasing of the Landing gear, with a time of 8.49 seconds, although it can vary depending on the operator. The advantages of this model include ease of operation, availability of easily obtainable materials, economical cost, and portability. Its drawbacks include inaccurate scale, material limitations, limited complexity, untested durability under extreme conditions, dependence on the operator, and the need for regular maintenance. Nonetheless, this model remains significant in aviation engineering education, helping students understand the Ground Lock main Landing gear mechanism through realistic simulations.